Flow splitting in numerical simulations of oceanic dense-water outflows. (May 2017) - Marques, Gustavo M.; Wells, Mathew G.; Padman, Laurie; Özgökmen, Tamay M.
Highlights: Idealized 2D, non-hydrostatic numerical simulations of oceanic outflows were performed. Conditions under which flow splitting may occur are identified using non-dimensional parameters. The mechanisms giving rise to the flow splitting are examined in detail. We hypothesized that flow splitting may occur in oceanic outflows with weak ambient stratification. Abstract: Flow splitting occurs when part of a gravity current becomes neutrally buoyant and separates from the bottom-trapped plume as an interflow. This phenomenon has been previously observed in laboratory experiments, small-scale water bodies (e.g., lakes) and numerical studies of small-scale systems. Here, the potential for flow splitting in oceanic gravity currents is investigated using high-resolution ( Δx = Δz = 5  m) two-dimensional numerical simulations of gravity flows into linearly stratified environments. The model is configured to solve the non-hydrostatic Boussinesq equations without rotation. A set of experiments is conducted by varying the initial buoyancy number B 0 = Q 0 N 3 / g ′ 2 (where Q 0 is the volume flux of the dense water flow per unit width, N is the ambient stratification and g ′ is the reduced gravity), the bottom slope ( α ) and the turbulent Prandtl number ( Pr ). Regardless of α or Pr, when B 0 ≤ 0.002 the outflow always reaches the deep ocean forming an underflow. Similarly, when B 0 ≥ 0.13 the outflow always equilibrates at intermediate depths, forming an interflow. However, when B 0 ∼ 0.016, flow splitting always occurs when Pr ≥ 10, while interflows always occur for Pr = 1. An important characteristic of simulations that result in flow splitting is the development of Holmboe-like interfacial instabilities and flow transition from a supercritical condition, where the Froude number ( Fr ) is greater than one, to a slower and more uniform subcritical condition ( Fr < 1). This transition is associated with an internal hydraulic jump and consequent mixing enhancement. Although our experiments do not take into account three-dimensionality and rotation, which are likely to influence mixing and the transition between flow regimes, a comparison between our results and oceanic observations suggests that flow splitting may occur in dense-water outflows with weak ambient stratification, such as Antarctic outflows.